2012
DOI: 10.1590/s1516-31802012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical, laboratory and treatment characteristics of spondyloarthritis patients with and without acute anterior uveitis

Abstract: CONTEXT AND OBJECTIVE: Acute anterior uveitis is a common extra-articular manifestation in spondyloarthritis patients. The aim of this study was to compare demographic, clinical, laboratory and treatment data among spondyloarthritis patients with and without acute anterior uveitis. DESIGN AND SETTING: This was a cross-sectional analytical study at the Rheumatology Outpatient Clinic of the Evangelical University Hospital, Curitiba, Brazil. METHODS: Spondyloarthritis patients with without acute anterior uveitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Consistent with the results of other groups of investigators (9,38,39,48), our data emphasize the existence of elevated values of BASDAI and BASFI in AAU AS patients suggesting that these patients develop a more aggressive disease than wAAU AS patients. For the first time, we identified MMP-2/sCD147 ratio as a new variable to better characterize AAU AS patients.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the results of other groups of investigators (9,38,39,48), our data emphasize the existence of elevated values of BASDAI and BASFI in AAU AS patients suggesting that these patients develop a more aggressive disease than wAAU AS patients. For the first time, we identified MMP-2/sCD147 ratio as a new variable to better characterize AAU AS patients.…”
Section: Discussionsupporting
confidence: 92%
“…44 The activity of uveitis is not necessarily correlated with the activity of systemic HLA-B27-associated disease. 45 The HLA-B27-associated AAU is typically unilateral and the intraocular inflammation usually lasts several weeks and diminishes within 3 months in the majority of patients. Occasionally, in severe cases, the time to remission may take longer than the 3 months, which is usually considered as a division border between acute and chronic forms of uveitis.…”
mentioning
confidence: 99%
“…One study has shown that history of uveitis is significantly associated with higher radiological score using Bath Ankylosing Spondylitis Radiology Index (BASRI). 16 On the other hand, Gehlen et al 5 have reported that BASRI scores are not significantly different between patients with or without uveitis (6.4±4.5 vs. 7.3±5.0, p=0.46) in a cross-sectional study. Chen et al 17 have also demonstrated that uveitis does not affect radiographic spinal involvement using both BASRI and mSASSS for patients in Taiwan.…”
Section: Discussionmentioning
confidence: 94%
“…4 Extra-articular manifestations of AS have also been frequently reported, with eyes being the most commonly involved. 5 Uveitis, inflammation of the anterior uvea containing iris and ciliary body, has been positively associated with disease progression of AS and occurs in 30 to 40% of patients with AS. [6][7][8] Symptoms of acute anterior uveitis (AAU) generally include an acute onset of eye redness and pain, intense photophobia, blepharospasm, and myosis that will eventually lead to reduction in visual acuity.…”
mentioning
confidence: 99%